2019
DOI: 10.20944/preprints201908.0037.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

P versus NP

Abstract: P versus NP is considered as one of the most important open problems in computer science. This consists in knowing the answer of the following question: Is P equal to NP? It was essentially mentioned in 1955 from a letter written by John Nash to the United States National Security Agency. However, a precise statement of the P versus NP problem was introduced independently by Stephen Cook and Leonid Levin. Since that date, all efforts to find a proof for this problem have failed. Another major complexity classe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…In this way, we obtain that L B / ∈ REG, since it is not possible that L B ∈ NSPACE(o(log log n)) under the result of L V B / ∈ NSPACE(S(n)) for all S(n) = o(log n) as a consequence of Theorem 15 when L = N L. Consequently, we obtain a contradiction just assuming that the Beal's conjecture is false and L B ∈ REG when L = N L. In contraposition, we have the Beal's conjecture is true or this has an infinite number of counterexamples both for a specific choice of exponents (x, y, z), since L B uses a specific choice of exponents (x, y, z) when L = N L. The Darmon-Granville theorem uses Faltings's theorem to show that for every specific choice of exponents (x, y, z), there are at most finitely many co-prime solutions for (A, B, C) [9], [11]. In conclusion, we obtain that necessarily the Beal's conjecture is true for this specific choice of exponents (x, y, z) as the remaining only option when L = N L. Since we took arbitrarily the exponents (x, y, z), then the Beal's conjecture will be true for every specific choice of exponents (x, y, z) when L = N L. On November 2019, Frank Vega proves that L = N P which also implies that L = N L [28], [29]. In this way, the Beal's conjecture is true.…”
Section: Theorem 16 the Beal's Conjecture Is Truementioning
confidence: 96%
“…In this way, we obtain that L B / ∈ REG, since it is not possible that L B ∈ NSPACE(o(log log n)) under the result of L V B / ∈ NSPACE(S(n)) for all S(n) = o(log n) as a consequence of Theorem 15 when L = N L. Consequently, we obtain a contradiction just assuming that the Beal's conjecture is false and L B ∈ REG when L = N L. In contraposition, we have the Beal's conjecture is true or this has an infinite number of counterexamples both for a specific choice of exponents (x, y, z), since L B uses a specific choice of exponents (x, y, z) when L = N L. The Darmon-Granville theorem uses Faltings's theorem to show that for every specific choice of exponents (x, y, z), there are at most finitely many co-prime solutions for (A, B, C) [9], [11]. In conclusion, we obtain that necessarily the Beal's conjecture is true for this specific choice of exponents (x, y, z) as the remaining only option when L = N L. Since we took arbitrarily the exponents (x, y, z), then the Beal's conjecture will be true for every specific choice of exponents (x, y, z) when L = N L. On November 2019, Frank Vega proves that L = N P which also implies that L = N L [28], [29]. In this way, the Beal's conjecture is true.…”
Section: Theorem 16 the Beal's Conjecture Is Truementioning
confidence: 96%
“…¿Cuándo es oportuna? Pedro de Vega sostuvo con brillantez que en «toda situación límite no cabe otro dilema que el de falsear la Constitución o reformarla», lo que equivale a indicar que «la necesidad jurídica…determina su conveniencia política» 69 . Pero me temo que no sea así muchas veces y no estoy seguro de que podamos seguir contemplando esta cuestión desde la razón teórica y el idealismo antes que desde la razón práctica.…”
Section: Una Teoría De Una Constitución Realizadaunclassified
“…On the other hand, seasonal variations of d( 18 O) and 17 O excess (D( 17 O) ¼ d( 17 O) À 0.52 Â d( 18 O) described by Barkan and Luz (2007)) depend on the nitric acid (HNO 3 ) production pathway from atmospheric NO x , with higher d( 18 (Hastings et al, 2004;Morin et al, 2008;Frey et al, 2009;Morin et al, 2012). Using bi-weekly measurements of d( 15 N) and D( 17 O), Morin et al (2008Morin et al ( , 2012 found a connection between low d( 15 N) and high D( 17 O) values as a consequence of NO x produced by local photochemical emissions from the snowpack that were later oxidized to NO 3 À by reactive halogens (e.g., BrO…”
Section: Introductionmentioning
confidence: 99%